Application of secondary intention for the restoration of the apical triangle after Mohs micrographic surgery. (19th May 2021) - Oh, Byung Ho; Oh, Yeongjoo; Nam, Kyoung Ae; Roh, Mi Ryung; Chung, Kee Yang
Abstract: Background: Restoring the apical triangle (AT) to maintain the symmetry of the face after Mohs micrographic surgery can be challenging. We have applied secondary intention (SI) after partial closure in cases with large defects. Objective: To compare the cosmetic results between immediate closure (IC) and SI. Methods & Materials: We retrospectively reviewed 24 patients (IC group: n = 15, SI group: n = 9). To evaluate the symmetry, the comparative ratio (CR; area of the AT of the involved side/area of the normal contralateral side) was calculated. Results: The defects were significantly larger in the SI group than in the IC group (588.89 ± 346.53 mm 2 vs. 252.87 ± 196.52 mm 2, p < .01). While there was no statistically significant difference in average CR, the standard deviation was higher in the SI group (0.95 ± 0.08 vs. 0.93 ± 0.31, p = .3359), indicating the difficulty in predicting the results of SI healing. The average visual analog scale score evaluated by two dermatologists was higher in the IC group, albeit without a significant difference (8.23 ± 0.96 vs. 7.78 ± 1.52, p = .5267). Conclusion: SI after partial closure can be an option for large defects in the AT area.